Inhibitory of Encapsulated Earthworm Extract (Lumbricus rubellus) on Pathogenic Bacteria in Vitro - L Istiqomah; H Herdian; E Damayanti; S N Hayati; H Julendra (Faculty of Animal Science, Bogor Agricultural University, 2012)
The objective of this study was to determine the inhibitory of earthworm (Lumbricus rubellus) extract (ECT) and encapsulated earthworm extract (ECT-t) as poultry feed additive against some pathogenic bacteria. Earthwom extract was prepared by dekokta method with water at 90 ºC then encapsulated by spray drying with maltodextrin as filler. In vitro antibacterial activity was performed using dilution method against Escherichia coli, Staphylococcus aureus, Salmonella pullorum, and Pseudomonas aeruginosa. The optical density results showed that started from ECT level 0.26% inhibited (PP. aeruginosa and S. aureus, while ECT level 0.52% inhibited (PE. coli and S. pullorum along with the increased levels of concentration. The percentage of growth showed that ECT level 1.04% had inhibitory (PE. coli and P. aeruginosa, while ECT level 0.52% showed antibacterial activity (PS. aureus. The result showed that S. aureus was the most sensitive bacterium to earthworms extract. ECT-t level 0.78% and 1.04% measured by spectrophotometer showed inhibitory (PP. aeruginosa and S. pullorum respectively. While ECT-t level 0.26% measured by spread plate count method showed inhibitory activity against P. aeruginosa. LD50 of E. coli and P. aeruginosa were found at ECT level 1.04%, while LD50 of S. aureus was found at level 0.52%. LD50 of P. aeruginosa was found at ECT-t level 0.52%. There were no antibacterial action (P>0.05) of ECT and ECT-t against S. pullorum.